Idiopathic Granulomatous Mastitis: An Autoimmune Disease?. (4th September 2013) - Altintoprak, Fatih; Karakece, Engin; Kivilcim, Taner; Dikicier, Enis; Cakmak, Guner; Celebi, Fehmi; Ciftci, Ihsan Hakkı
Abstract : Purpose . This study aimed to investigate the autoimmune basis of idiopathic granulomatous mastitis (IGM) by determining the anti-nuclear antibody (ANA) and extractable nuclear antigen (ENA) levels of patients diagnosed with IGM. Material and Methods . Twenty-six IGM patients were evaluated. Serum samples were analyzed for autoantibodies by indirect immunofluorescence (IIF) using a substrate kit that induced fluorescein-conjugated goat antibodies to human immunoglobulin G (IgG). IIF patterns were read at serum dilutions of 1 : 40 and 1 : 100 for ANA positivity. Using the immunoblot technique, the sera of patients were assayed at dilutions of 1 : 40 and 1 : 100 for human autoantibodies of the IgG class to 15 lines of highly purified ENAs. Results . In the IIF studies for ANA, positivity was identified for four different patterns in the 1 : 40 diluted preparations, for three different patients in the 1 : 100 diluted preparations and only one pattern was identified at the 1 : 320 dilution. In the ENA studies, positivity was identified for four different pattern in the 1 : 40 dilution, and only one pattern was identified at the 1 : 100 dilution. Conclusion . This study was not able to support the eventual existence of an autoimmune basis for IGM.